Range extension of the Macroglossum pyrrhosticta Butler, 1875, in Northwestern India (Lepidoptera: Sphingidae) - Shahabab A. Farooqui; Ian J. Kitching; Hina Parwez; Rahul Joshi (SHILAP, 2022)
During a faunistic survey of Lepidoptera in Sasni (27.7063º N, 78.0823º E; 181 m), Uttar Pradesh, a specimen of Macroglossum pyrrhosticta Butler, 1875, was collected and thus the species reported for the first time from the Gangetic Plains Biogeographic Zone of India, as well as North-West India as a whole. Details of the known larval host plants of M. pyrrhosticta are also provided, together with a checklist of the Indian species of genus Macroglossum Scopoli, 1777.